ARAH PENDIDIKAN ISLAM ANAK USIA DINI - Tanjung, Zulkifli (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The function of education is very strategic in optimizing children's development from an early age to higher education. For this reason, the implementation of Islamic education for early childhood is the responsibility of parents, schools and the community in developing the potential of early childhood so that they have an Islamic character that is reflected in akidah, worship, morals and mu'amalah. Cultivating the values ​​of monotheism, worship and morals are fundamental along with speaking, motoric and scholastic exercises. Thus, every parent needs to play an effective role to ensure that early childhood is the target of Islamic education which is obliged to receive early and sustainable care, education and guidance services.